Tindak Pidana Diskriminasi Terhadap Anak Akibat Perceraian Orangtua - Syarifuddin Syarifuddin (Universitas Islam Sumatera Utara, 2018)
AbstractLegal protection for children is constitutionally guaranteed under Article 28 paragraph (2) of the 1945 Constitution of the Republic of Indonesia and strengthened through the ratification of the International Convention on the Rights of the Child, namely the Ratification of the Convention on the Rights of the Child through Presidential Decree Number 36 of 1990 concerning the Ratification of the Convention On The Rights of The Child (Convention on the Rights of the Child. The State, Government, Regional Government, Community, Family and Parents are obliged and responsible for the implementation of child protection to ensure the fulfillment of children's rights based on their duties and responsibilities. Protection of children must be able to provide guarantees for children to live, grow, develop in accordance with their dignity, and give children the right to express and hear their opinions in accordance with their age and level of intelligence with the principle of the best interests for children. Divorce done by parents has a negative impact on the child's growth and development, both physically and psychologically. Due to the parent's attitude, the child will become a victim for quite a long time; especially when the child is unable to go through the transition from the family condition,it will make child victim of the umpteenth time due to the behavior / attitude of adults (his own parents). Discrimination against children causes a child to suffer material or moral losses that impede his social function so that the offender can be convicted of discrimination against children. Keywords: discrimination, child, divorce